2021
DOI: 10.1039/d0gc04108d
|View full text |Cite
|
Sign up to set email alerts
|

Levulinic acid hydrogenation to γ-valerolactone over single Ru atoms on a TiO2@nitrogen doped carbon support

Abstract: The transformation of levulinic acid(LA) to γ-valerolactone (GVL) in water at room temperature is very interesting. In this work, we designed and prepared single Ru atoms on TiO2@nitrogen droped porous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 61 publications
0
31
0
Order By: Relevance
“…In addition, we can further confirm that the metals Ni and Ru are present partially in the form of metal oxides according to the presence of lattice O species in Ru(Ni)–O bonds. 34,35…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we can further confirm that the metals Ni and Ru are present partially in the form of metal oxides according to the presence of lattice O species in Ru(Ni)–O bonds. 34,35…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we can further conrm that the metals Ni and Ru are present partially in the form of metal oxides according to the presence of lattice O species in Ru(Ni)-O bonds. 34,35 In order to obtain the true metal loadings of catalysts, the ICP-AES analysis was executed and the results are listed in Table 2. Compared with the initial 78.8 wt% of Ni@C, the most Ni loss rate of 11.2 wt% was observed for Pt/Ni@C. In addition, the Pt agglomeration spots of Pt/Ni@C can be observed in TEM images (Fig.…”
Section: Catalytic Performancementioning
confidence: 99%
“…This results indicated that N doping can secure Pd NPs on their original position and inhibit the growth of Pd NPs. 43,44 In addition, the surface area of Pd/AC-500 and Pd/N_AC-500 was 921.2 and 940.6 m 2 g À1 , and the corresponding pore volume was 0.488 and 0.489 cm 3 g À1 respectively. The surface area and pore volume of aged samples slightly increased compared with the fresh ones.…”
Section: Stability Of Pd Catalystsmentioning
confidence: 99%
“…For example, Zhang et al prepared a single-atom Ru/ TiO 2 @CN catalyst using the pyrolysis technique where NH 2 -MIL-125 MOF was used as the precursor. 55 The striking fact was that the catalyst could completely convert LA into GVL with 100% selectivity at room temperature in water. Compared to the benchmark Ru/C catalyst, the Ru SAC showed 35 times higher activity with a TOF of 278 mol GVL mol Ru −1 h −1 .…”
Section: Hydrogenation Reactionsmentioning
confidence: 99%